Smar2C2: A Simple and Efficient Protocol for the Identification of Transcription Start Sites. Issue 3 (22nd March 2023) - Murray, Andrew; Vollmers, Christopher; Schmitz, Robert J.
Abstract: Promoters and the noncoding sequences that drive their function are fundamental aspects of genes that are critical to their regulation. The transcription preinitiation complex binds and assembles on promoters where it facilitates transcription. The transcription start site (TSS) is located downstream of the promoter sequence and is defined as the location in the genome where polymerase begins transcribing DNA into RNA. Knowing the location of TSSs is useful for annotation of genes, identification of non‐coding sequences important to gene regulation, detection of alternative TSSs, and understanding of 5′ UTR content. Several existing techniques make it possible to accurately identify TSSs, but are often difficult to perform experimentally, require large amounts of input RNA, or are unable to identify a large number of TSSs from a single sample. Many of these protocols take advantage of template switching reverse transcriptases (TSRTs), which reliably place an adaptor at the 5′ end of a first strand synthesis of cDNA. Here, we introduce a protocol that exploits TSRT activity combined with rolling circle amplification to identify TSSs with several unique advantages over existing methods. Sequence adaptors are placed on the 5′ and 3′ end of the full‐length cDNA copy of a transcript. A splint compatible with those adaptors is then used to circularize the full‐length cDNA. Linear DNA containing concatemers of the cDNA are generated using rolling circle amplification, and a sequencing library is formed by fragmenting the concatemers. This protocol is straightforward to execute, requiring limited bench time with relatively stable reagents. Using extremely low amounts of RNA input, this protocol produces large numbers of accurate, deduplicated TSSs genome wide. © 2023 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Splint generation Basic Protocol 2 : RNA extraction Basic Protocol 3 : cDNA synthesis Basic Protocol 4 : cDNA circularization and amplification Basic Protocol 5 : Library generation